2006
DOI: 10.1590/s1516-44462006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of evidence-based practices for children in four countries: a project of the World Psychiatric Association

Abstract: A b s t r a c t Objective: The present study examined implementation issues in adopting cognitive-behavioral therapies in routine clinical settings in four countries reflecting diverse cultures, languages, settings, and traditions. Method: A Director's Systems Survey was administered prior to program implementation and one year later. Therapist ratings on attitudes about evidence-based practices and satisfaction were also gathered. Results: All sites reported successful adoption of the program, although signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…The importance of aligning school philosophy, goals, policies, and other programs with a newly adopted intervention is consonant with other studies suggesting that the ''fit'' of a program to its context is important (Hoagwood, Kelleher, Murry, & Jensen, 2006). A high-quality program with clear evidence of positive impact may nevertheless be a poor match for an individual school.…”
Section: Discussionmentioning
confidence: 81%
“…The importance of aligning school philosophy, goals, policies, and other programs with a newly adopted intervention is consonant with other studies suggesting that the ''fit'' of a program to its context is important (Hoagwood, Kelleher, Murry, & Jensen, 2006). A high-quality program with clear evidence of positive impact may nevertheless be a poor match for an individual school.…”
Section: Discussionmentioning
confidence: 81%
“…International chapters are beginning to be formed, particularly for families of children with specific disorders, such as ADHD, autism, and bipolar disorders (Hoagwood et al 2006).…”
mentioning
confidence: 99%
“…Our distance training/supervision model provided a blueprint for future international training programs. As discussed by Hoagwood et al, 22 high ratings were found on therapist's satisfaction towards training and consultation, treatment acceptability, and the likelihood that they would use the treatment in the future. Nevertheless, some limitations to this study should be noted.…”
Section: O N C L U S I O Nmentioning
confidence: 94%